α-SNAP Prevents Docking of the Acrosome during Sperm Exocytosis because It Sequesters Monomeric Syntaxin - Rodríguez, Facundo (Public Library of Science, 2011)
α-SNAP has an essential role in membrane fusion that consists of bridging cis SNARE complexes to NSF. α-SNAP stimulates NSF, which releases itself, α-SNAP, and individual SNAREs that subsequently re-engage in the trans arrays indispensable for fusion. α-SNAP also binds monomeric syntaxin and NSF disengages the α-SNAP/syntaxin dimer. Here, we examine why recombinant α-SNAP blocks secretion in permeabilized human sperm despite the fact that the endogenous protein is essential for membrane fusion. The only mammalian organism with a genetically modified α-SNAP is the hyh mouse strain, which bears a M105I point mutation; males are subfertile due to defective sperm exocytosis. We report here that recombinant α-SNAP-M105I has greater affinity for the cytosolic portion of immunoprecipitated syntaxin than the wild type protein and in consequence NSF is less efficient in releasing the mutant. α-SNAP-M105I is a more potent sperm exocytosis blocker than the wild type and requires higher concentrations of NSF to rescue its effect. Unlike other fusion scenarios where SNAREs are subjected to an assembly/disassembly cycle, the fusion machinery in sperm is tuned so that SNAREs progress uni-directionally from a cis configuration in resting cells to monomeric and subsequently trans arrays in cells challenged with exocytosis inducers. By means of functional and indirect immunofluorescense assays, we show that recombinant α-SNAPs — wild type and M105I — inhibit exocytosis because they bind monomeric syntaxin and prevent this SNARE from assembling with its cognates in trans. Sequestration of free syntaxin impedes docking of the acrosome to the plasma membrane assessed by transmission electron microscopy. The N-terminal deletion mutant α-SNAP-(160–295), unable to bind syntaxin, affects neither docking nor secretion. The implications of this study are twofold: our findings explain the fertility defect of hyh mice and indicate that assembly of SNAREs in trans complexes is essential for docking.